Penggunaan Bahasa Dalam Mengekspresikan Emosi Kegembiraan Siswa Diniyah Takmiliyah Awaliyah Pasca Gempa (Kajian Psikolinguistik) (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
The purpose of this research is to identify, analyze, and describe language as a form of emotional expression, especially the joy of DTA students who feel the earthquake in the Cianjur Regency area. The method used in this research is descriptive method. The object of research is DTA students who touch the earthquake. All data was taken from the language process of DTA students during the research process which expressed joyful emotions. The results of the analysis showed that there were several emotional expressions of students' joy after being given several treatments in the form of traditional games. The actualization of students in expressing the emotion of joy is shown by verbal expressions and followed by gestures as a form of overflowing joy that is in them.